Akad Ijarah Pada Praktik Pemberian Upah Jasa Penggali Kubur Di Desa Yosorejo Kabupaten Batang Dalam Perspektif ‘Urf - Mufarikha, Azka; Inayati, Anindya Aryu; Rosyid, Irkham Abdul (el hisbah Journal of Islamic Economic Law, 2022)
Every human being cannot fulfill his needs without other people. So, Allah ordered His servants to fulfill the help. Human relations according to Islamic law are muamalah. In general, wages are the agreed total amount of replacement services determined by workers covering certain periods and conditions. This study aims to explain the practice of giving grave diggers wages in Yosorejo Village, Batang Regency in the 'Urf Perspective and to analyze the Conformity between the Ijarah Agreement and the Practice of Grave Digger Service Wages in Yosorejo Village, Batang Regency. This type of research is a socio legal research approach or empirical legal research and a conceptual approach. Primary data sources were obtained from observations and interviews by gravediggers and the community. Sources of secondary data obtained from research journals, previous research, and fiqh books related to research problems obtained by documentation techniques. Data analysis is carried out continuously. The results of this study indicate that the practice of providing wages for gravediggers in Yosorejo Village, it appears that the practice of wages is an inherent and long-standing tradition. Tradition in a society is a custom that is not easy to abolish or replace with new habits.